IMUNITAS TERHADAP PEJABAT PEMERINTAH INDONESIA DAN AMERIKA KETIKA PANDEMI COVID-19, SERTA IMPLIKASINYA TERHADAP PENERAPAN DAN PENEGAKAN ASAS UMUM PEMERINTAHAN YANG BAIK - Richard Jatimulya Alam Wibowo; Tundjung Herning Sitabuana (Fakultas Hukum Universitas Tarumanagara, 2021)
The COVID-19 pandemic on a global scale requires governments of countries to find solutions to address the economic, social, and public health impacts. This study uses a statutory and comparative approach, by tracing primary, secondary, and jurisprudential sources of law. In administering the government during the COVID-19 pandemic, government officials get legal protection, so they are not haunted by fear of legal entanglement in making decisions as long as they are based on good faith. Furthermore, the government in this case is guided by the General Principles of Good Governance in forming decisions that become the legal basis for dealing with problems during the COVID-19 pandemic. Whereas then, the existence of the right to immunity during the pandemic, as well as the enforcement, and the doctrine of the General Principles of Good Governance in Indonesia and the United States have constitutional contrasts. Therefore, this study then found similarities and differences in the practice and substance of granting immunity and the doctrine of the General Principles of Good Governance in Indonesia and the United States of America, according to the different law system, social, and culture